The Fire in The Flint: Arrowhead Production and Heat Treatment - Diana Coles (Internet Archaeology, 2009)
In 2004 David Clark wrote of the concentrations of arrowheads found at a number of sand dune sites in Scotland that 'at present we have no narratives that seek to explain, or even acknowledge this situation.' This paper seeks, through an exploration of the manufacturing processes involved in producing a particular arrowhead from Luce Sands, Wigtownshire, to provide some of the detail to allow the construction of a wider narrative.